Generation of heterozygous SAMD9 CRISPR/Cas9-edited iPSC line (ESi086-A-3), carrying p.I1567M mutation - Joan Pera; Julio Castaño; Joan Casamitjana; Alessandra Giorgetti; Damia Romero-Moya (Stem Cell Research, 2022)
Germline SAMD9 mutations are one of the most common alterations that predispose to pediatric myelodysplastic syndrome (MDS), a clonal disorder characterized by ineffective hematopoiesis, increasing the risk of developing acute myeloid leukemia (AML). Up to date, a disease model to study the role of SAMD9 mutation in MDS is still lacking. Here, we have generated a human induced pluripotent stem cell (hiPSC) line carrying SAMD9mut (p.I1567M), taking advantage of CRISPR/Cas9 system. As a result, the genetic engineered hiPSC line represent a new in vitro disease model to understand the impact of SAMD9 mutation at molecular and cellular level during hematopoiesis.